Design and stereoselective synthesis of novel β-lactone and β-lactams as potent anticancer agents on breast cancer cells. Issue 8 (22nd February 2018) - Rashidi, Mahnoosh; Islami, Mohammad Reza; Esmaeili-Mahani, Saeed
Abstract: To produce a novel class of anticancer compounds, an efficient method for synthesizing novel β-lactone and β-lactam frameworks was developed based on the reaction of a new ketene with C=O and C=N bonds. Functionalized 2-azetidinones were efficiently synthesized by employing 2, 4-dichlorophenoxylketene, which was generated in situ. The reaction of the ketene with aldehydes was not successful and in all cases except for 4-nitrobenzaldehyde, a rearranged dimer of the ketene was obtained as a lactone. Anticancer cellular activity of all new β-lactams and lactones on breast cancer cells was studied. All new synthesized compounds exhibited potential anticancer activity which may guarantee their future application in moderate chemotherapy. Graphical abstract: